Analysis of microbiota in the stomach and midgut of two penaeid shrimps during probiotic feeding - Kentaro Imaizumi (Nature Portfolio, 2021)
Abstract In mammals, the intestine harbors numerous bacteria that play an important role in health. Intestinal microbiota have also been thought to be an important factor in the health of shrimp. However, the barrier systems of the digestive tracts of shrimp seem to be different from those of mammals. In this study, we analyzed the bacterial composition in the stomach and midgut of two species of shrimp during administration of a probiotic, Bacillus amyloliquefaciens strain TOA5001 by analysis of 16S rRNA genes with Illumina sequencing technology. Whiteleg shrimp Litopenaeus vannamei were observed under laboratory conditions and kuruma shrimp Marsupenaeus japonicus were observed in an aquaculture farm. The diversities of bacteria in the stomachs of both shrimps were significantly higher than those in the midgut. Also, the microbiota changed during probiotic feeding. Feeding whiteleg shrimp the probiotic after being challenged with an acute hepatopancreatic necrosis disease (AHPND)-causing strain of Vibrio parahaemolyticus increased their survival compared to the control group, which suggested that the probiotic prevented AHPND. These results appear to show that a probiotic can affect the microbiota throughout digestive tract of penaeid shrimps and that probiotic can have a role in preventing disease.